An experimental study of how missing employee empathy in failed service interactions affects empathetic customers' ewom-giving behaviour - Neele Inken Abend; María D. de Juan Vigaray; Mandy Nuszbaum (Administrative Sciences, 2023)
Empathy as an influencing factor of consumer behaviour has mostly been analysed from an empathetic employee's perspective. Empirical investigations into customer empathy in the context of failed service interactions are still scarce. This study investigates customer-employee reciprocity related to a failed service interaction and its meaning as a predictor of electronic-worth-of-mouth (eWoM)-giving behaviour. The eWoM phenomenon in the context of online purchases is well researched, but the (a) impact of failed service interactions and (b) empathetic customer service agents still needs to be explored. For this purpose, two situational experiments of customer-employee interactions (n = 260) were conducted. Both situations depict disgruntled customers who are looking for help and call the customer support centre after an online purchase. They experience negative customer-employee interaction. The experiments test (a) the impact of employee and customer empathy on eWoM-giving behaviour after failed service interactions and (b) the mediating role of negative emotions. The results show that in service situations, negative emotions fully mediate the relationship between customer empathy and eWoM-behaviour. In addition, empathetic customers seem to be more sensitive to a poorly empathetic employee in comparison to non-empathetic customers. The research enriches the service understanding of empathy in eWoM research and provides practical implications for the management of complaint handling, such as how to consider customer empathy as a complainer's characteristic to improve the customer service experience, effectiveness, and efficiency.
Keywords: 350; complaint behaviour; customer behaviour; customer empathy; customer service; electronic-worth-of-mouth; emotional intensity; failed service interaction; service failure